The Effect of Service Innovation and Affective Services on The Accessibility of Information and Decisions To Visit of The Tour Boat Service Users in Pesut Etam, Samarinda - Syarifah Hudayah; Herning Indriastuti; Noris Marten Polanco (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
This study aims to examine the effect of service innovation and Affective Services on the decision to visit with the accessibility of information as a mediating variable in the tourist boat service users in Pesut Etam, Samarinda. The approach used in this study is the quantitative approach. The sample used in this study were visitors of Pesut Etam, Samarinda with a total of 170 respondents. The research Data were obtained from the questionnaire and analyzed using SEM PLS analysis techniques with the help of the SmartPLS program. The results of this study indicate that service innovation directly or indirectly through the accessibility of information has a positive and significant effect on the decision to visit, the better the service innovation in tourist boat services in Pesut Etam tourism object, the better the accessibility of information and decisions of tourists using the services of the tourist boat, and vice versa the lack of service innovation will inhibit the accessibility of information which will further reduce the decision of tourists using the services of the tourist boat. The results of the second analysis in this study is that Affective Services can not directly affect the decision to visit but, are mediated by the accessibility of information, Affective Services can affect the decision to visit. This means that just good affective service is not enough to improve the decision to visit. Affective Services that exist can improve visiting decisions if the service can support the accessibility of information about the tourist ship services.